Situation Report: Czechoslovakia, 15 October 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Czechoslovakia Presses on with the CMEA Summit Idea Slovak Daily Attacks Pope, Links Wyszynski with Fascism End of Subsidies for Slovakia Grain Harvest Quota Not Met Environmental Protection - A Vital Challenge Minister of Labor Issues Lamentations and Warnings The CSSR Is Considered Imperiled by the Corruption of the Young